2011
DOI: 10.14203/risetgeotam2011.v21.47
|View full text |Cite
|
Sign up to set email alerts
|

Dinamika Elevasi Muka Air Pada Lahan Dan Saluran Di Lahan Gambut

Abstract: ABSTRAK Reklamasi gambut untuk pertanian memerlukan jaringan drainase makro yang dapat mengendalikan tata air dalam satu wilayah dan drainase mikro untuk mengendalikan tata air di tingkat lahan. Elevasi muka air harus dipertahankan secara optimal. Tidak terlalu dalam agar tanaman tidak mengalami kekeringan dan tidak terlalu dangkal agar tanaman tidak tergenang. Untuk itu diperlukan bangunan pengendali berupa pintu air di setiap saluran. Pintu air berfungsi untuk mengatur muka air tanah supaya tidak terlalu dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Excessive drying with drainage directly impacts the decrease in groundwater level (Huijnen et al 2016;Koh et al 2011). Drainage development causes the function of peat hydrological systems as reservoirs and water management to be reduced or even lost (Radjagukguk 1997;Runtunuwu et al 2011). In addition, continuous drainage results in an irreversible drying process.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive drying with drainage directly impacts the decrease in groundwater level (Huijnen et al 2016;Koh et al 2011). Drainage development causes the function of peat hydrological systems as reservoirs and water management to be reduced or even lost (Radjagukguk 1997;Runtunuwu et al 2011). In addition, continuous drainage results in an irreversible drying process.…”
Section: Introductionmentioning
confidence: 99%
“…Fluctuations in the quantity and quality of food villagers consume, such as labor shortages and climatic conditions, are common. Historical meteorological data show frequent above-average droughts and floods (Runtunuwu et al, 2011). For example, a 2015 study in Batu City, Malang Province, found that farmers reported stopping agricultural activities during the dry season (Chiari, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Fluctuations in the quantity and quality of food villagers consume, such as labor shortages and climatic conditions, are common. Historical meteorological data show frequent above-average droughts and floods (Runtunuwu et al, 2011). For example, a 2015 study in Batu City, Malang Province, found that farmers reported stopping agricultural activities during the dry season (Chiari, 2015).…”
Section: Discussionmentioning
confidence: 99%